Asian Growth and African Development - Chamon, Marcos de Carvalho; Kremer, Michael R (American Economic Review, 2006)
Since World War II, integration with the world economy has arguably been the chief route from poverty to wealth. Japan initially exported cheap goods and later moved on to more technologically sophisticated products. When Japan became rich, Korea, Taiwan Province of China, Hong Kong SAR, and Singapore replaced Japan as low-wage exporters, and when these countries moved on to more sophisticated products, Thailand and Malaysia filled their niche. More recently, China has become an important exporter of manufactured goods and India is increasingly moving into services exports. No mainland sub-Saharan African country has experienced this type of transformation. Even countries that have undergone major economic reforms seem far from takeoff. Forecasts for Africa, based on extrapolation of its historical experience, tend to be bleak. We consider whether it is possible to construct a model, consistent with the data, which supports a more optimistic view. Motivated by the Asian experience, the model assumes countries can potentially undergo rapid economic transformation only if they integrate into the world economy by producing nontraditional exports. For the purposes of constructing a long-run model of the world economy, we are agnostic on whether exports matter due to technological learning by doing spillovers, political economy considerations, or other factors. As each developing country transforms and becomes advanced, it further improves trade opportunities for the remaining developing countries. For example, if China becomes rich, a billion more people will live in countries that import toys and a billion fewer will live in countries that export them. Our approach is similar to that of Robert E. Lucas (2000) in that we assume growth prospects improve with the state of the world economy, potentially generating accelerating world growth. Unlike Lucas (2000), however, we allow for differential population growth between rich and poor countries. The steady-state proportion of the world population living in advanced countries depends on the rate at which developing countries transform into advanced ones, and on the magnitude of population growth differentials between these two groups of countries. The economic transformation process will overcome the demographic trend, leading to a prosperous steady state, only if the initial share of world population in advanced countries is above a threshold. A simple calibration using historical data suggests that the longrun prospects for lagging developing regions may hinge on a race between economic growth in China and India and population growth in the lagging regions, particularly Africa. If the former “wins,” we may eventually observe accelerating global growth. This suggests some caution should be used when interpreting empirical studies on growth determinants, as these results may not be stable over time. Country characteristics that lead to poor performances today may well allow for rapid growth in the future if, and when, the world economy reaches a sufficiently advanced stage. Our model also suggests a queuing effect, where the order in which countries are absorbed into the world economy is determined by the quality of their policies. Economic reforms in one country may potentially have a large impact on growth if they move the country to the front of the queue. But similar reforms in all countries may have a much smaller impact on world growth.